Política externa dos Estados Unidos para as mudanças climáticas: do estabelecimento à retirada dos Estados Unidos do acordo de Paris - Mendes, Xavier Sanca (2024)
The study in question analyzes the United States' approach to global climate policies, emphasizing its role in the negotiations that culminated in the formation of the Paris Agreement and subsequent withdrawal from the treaty. The objective was to understand the United States' stance during the deliberations of the Paris Agreement, the reasons for its withdrawal from the agreement and the implications of this decision for international strategies to combat global warming. It is based on the hypothesis that the economic issue, the climate denialism of some entities, especially the American right, the electoral promises and the refusal of historical responsibility for the emissions of gases harmful to the environment, the agribusiness, oil and gas lobbies, form a set of factors that help explain the reason for the abandonment of the Paris Agreement by the Trump administration. The exploratory investigation revealed that the influence of the United States was decisive in structuring the Paris Agreement. However, the decision to withdraw from the agreement, taken by then President Donald Trump, reflects a series of internal elements in the United States, with emphasis on the pressure exerted by the fossil fuel industries.